The performance and motivation of serial acquisitions: Evidence from Australia - Hossain, M.M.; Pham, M.D.; Islam, Nahid (ELSEVIER SCIENCE INC, 2021)
Using 2696 acquisition announcements reported in Australia between 2000 and 2016, we document lower stock returns but higher risk for deals made by serial acquirers compared to those made by single acquirers after controlling for firm and deal characteristics. We also find that serial acquirers' underperformance relative to single acquirers is more pronounced when managers gain more control over their firm's resources. Further analysis reveals that the outcome of the first transactions is key to deriving serial acquisitions' motivation and performance.